Metallographic analysis of the internal microstructure of orthodontic mini-implants - Flávio Augusto Cotrim-Ferreira; Camila Leite Quaglio; Rubén Patricio Vásquez Peralta; Paulo Eduardo Guedes Carvalho; Danilo Furquim Siqueira (Sociedade Brasileira de Pesquisa Odontológica, 2010)
Effective orthodontic anchorage may be obtained by miniimplants inserted into the maxillary bones. However, the risk of miniimplant failure is one of the most important issues, especially the rupture of its structure referred to as fracture, mainly due to metal deficiencies. This study analyzed the internal microstructure of orthodontic mini-implants, ascertaining the composition of the metal to detect possible discontinuities from the surface to the core of the screws. Eighteen samples of mini-implants, of 3 different brands, were obtained. The samples were cold-embedded in methyl methacrylate polymer, and were sectioned both longitudinally (3 samples of each brand) and transversely (the other 3 screws of each brand). After preparation, the samples were observed using a light microscope at up to 2,000 x magnification. The results showed that the mini-implants thus analyzed were composed of an Alpha-Beta globular phase of titanium alloy, patterns A1 and A9 (in accordance with the "Technical Committee of European Titanium Producers"). The miniimplants did not present any defects such as bubbles, imperfections or fissures, in either longitudinal or transverse sections, in their internal microstructure. All samples met the requirements of international norms. Orthodontists must be aware of the metal composition and internal microstructure of mini-implants, to decrease the risk of fractures.